Pengembangan Multimedia Pembelajaran Interaktif Berbasis Etnomatika pada Materi Bangun Datar untuk Siswa Kelas II SD - Urip Umayah (Journal on Education, 2023)
This study aims to produce interactive multimedia based on ethnomatics in flat shape material for second grade elementary school students. This type of research is research R & D (Research and Development). The development model used is Alessi & Trollip. The results of the media expert's assessment on the display and programming aspects were in the good category and the material experts on the content and learning aspects were in the very good category. The average score of the assessment results in the small, medium and large groups was > 88, meaning that the quality aspects of the product by users were in the good category. The research subjects were 21 grade II students at SDN Adipala 5. The result obtained is the NGain value of 0.91, which means that this ethnomatics-based interactive multimedia is effective in improving flat shape material for class II students. This is because the way the material is presented in the media gives students the opportunity to explore their abilities. Through this media students are able to explain how to measure angles in writing (writing), students can draw angles (drawing), and are able to use formulas to determine the size of angles in flat figures (expression mathematics). Based on the results of the research and discussion, it can be concluded that interactive learning multimedia meets the feasible category, so that it can be used in the learning process.